2005
DOI: 10.1108/09513570510588733
|View full text |Cite
|
Sign up to set email alerts
|

Balancing money and mission in a local church budget

Abstract: Purpose. This study of budgeting practices and attitudes to budgeting in a local church uses framework to consider the potential conflict between the "sacred" agenda of the church and the "secular" nature of accounting. Design/methodology/approach. Over a six month period, the author conducted a series of semi-structured interviews with key church leaders, and studied financial reports and the minutes of church meetings. Findings. Clergy and lay people alike, far from viewing accounting as an unwelcome intrus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
1
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 25 publications
2
87
1
3
Order By: Relevance
“…We also found a large number of volunteers in our study. Similar findings were evident in studies by Duncan et al (1999), Wooten et al (2003), Bowrin (2004) and Irvine (2005). This is because nonprofit organizations tend to be heavily dependent on volunteers.…”
Section: Analysis and Findings Demographic Profilesupporting
confidence: 77%
See 1 more Smart Citation
“…We also found a large number of volunteers in our study. Similar findings were evident in studies by Duncan et al (1999), Wooten et al (2003), Bowrin (2004) and Irvine (2005). This is because nonprofit organizations tend to be heavily dependent on volunteers.…”
Section: Analysis and Findings Demographic Profilesupporting
confidence: 77%
“…Accountants may give advice but they should not be put in control. Irvine (2005) also found that the need for accounting to achieve the sacred mission of the church organization is pertinent. Thus, the resistance to accounting, in principle, is minimal.…”
Section: Between the Sacred And The Secularmentioning
confidence: 99%
“…This practice is also suggested to be practiced by CLBG A and CLBG C as it will increase the accurate management of Islamic charity funds based on the donors' preference. By having good practice in documentation and records, it will lead to more reliability, especially for audit process and give more assurance for financial disclosure (Irvine 2005;Shiri et al 2012;Spitzer 2005).…”
Section: Documentation and Recordsmentioning
confidence: 99%
“…This is due to the set up requirement by the CCM for every company including CLBG type to submit audited financial statements annually to them. By having the audit process, it is also required for these three CLBGs to have an adequate and reliable financial documentation and records (Irvine 2005;Shiri et al 2012;Spitzer 2005). Thus, this shows that all three CLBGs comply with the independent checks on the performance element for control activities.…”
Section: Independent Checks On Performancementioning
confidence: 99%
“…Walaupun tidak lazim, penelitian praktik akuntansi pada lembaga keagamaan se perti gereja banyak dilakukan oleh beberapa peneliti akuntansi. Salah satu peneliti (Irvine 2005) menyimpulkan bahwa pendeta dan orang awam percaya akuntansi tidak mengganggu agenda suci yang dikerjakan oleh gereja. Sebaliknya, akuntansi merupakan bagian penting yang terintegrasi dengan kepentingan gereja demi mencapai misi kudus karena temuan ini berkepentingan dengan masyarakat sebagai sumber keuangannya dalam bentuk sumbangan, sedekah atau bentuk bantuan sosial lainnya yang berasal dari masyarakat (publik).…”
unclassified